Features of interpersonal relations of contemporary adolescents with peers as conditions for their personal development (Actual Problems of Psychology in Educational Institutions, 2022)
This article is dedicated to the issue of interpersonal relations between adolescents and peers. It presents the results of theoretical analysis and empirical research of the features of interpersonal relations of contemporary adolescents with peers as conditions for their personal development.